Purinergic Antagonism Prevents Mitochondrial Dysfunction and Behavioral Deficits Associated with Dopaminergic Toxicity Induced by 6-OHDA in Rats - Kumar S.; Mishra A.; Krishnamurthy S. (My University, 2025)
Purinoceptors are present in neurons, microglia and oligodendrocytes and regulate dopamine (DA) release, striatal-related function and striatal neuronal and DA cells damage. Therefore, purinoceptors may be involved in the pathology of Parkinson’s disease (PD) and purinergic antagonism may show neuroprotective effect. The study investigated the role of the non-selective purinergic receptor antagonist pyridoxalphosphate-6-azophenyl-2′, 4′-disulfonic acid (PPADS) and a selective purinergic receptor P2X7 receptor antagonist Brilliant Blue G (BBG) against 6-OHDA induced dopaminergic neurotoxicity in rats; while adenosine triphosphate (ATP) was used as a P2X receptor agonist. Behavioral parameters like spontaneous motor activity, narrow beam walk, footprint, bar catalepsy, grip strength and rotarod tests were performed to evaluate motor deficits in PD. Striatal DA contents were estimated as neurochemical measures of PD. Mitochondrial studies and oxidative status were assessed to investigate the mechanism of purinergic system antagonists. Involvement of purinergic receptors in apoptosis was assessed by expressing cytochrome-C, caspase-9 and caspase-3. Both the antagonists not only attenuated 6-OHDA induced motor deficits but also protected against 6-OHDA induced DA depletion in the striatum. Oxidative stress, mitochondrial integrity and dysfunction were attenuated by purinergic antagonists. Further, they attenuated mitochondrial-linked apoptosis as observed by a decrease in expression of cytochrome-C, caspase-9 and caspase-3. Therefore, purinoceptor antagonism shows neuroprotective effect in 6-OHDA induced dopamine toxicity through preservation of mitochondrial bioenergetics and anti-apoptotic activities. © 2017, Springer Science+Business Media, LLC.